2021
DOI: 10.3762/bjoc.17.153
|View full text |Cite
|
Sign up to set email alerts
|

Advances in mercury(II)-salt-mediated cyclization reactions of unsaturated bonds

Abstract: The synthesis of complex cyclic compounds is extremely challenging for organic chemists. Many transition-metal-salt-mediated cyclizations are reported in literature. Hg(II) salts have been successfully employed in cyclizations to form complex heterocyclic and carbocyclic structures that are impossible to synthesize with other transition metal salts. In this review, we have summarized cyclization reactions that are performed with Hg(II) salts. These salts are also successfully applied in stoichiometric or catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…A large number of cyclizations are produced via transition-metal salts. Complex heterocyclic and carbocyclic compounds, which are hard to manufacture with other transition metal salts, have been successfully synthesized via cyclizations involving Hg( ii ) salts 22 Methane is converted into methanol not just in the presence of HgCl 2 . 23 But mercuric sulfate is also used as a catalyst.…”
Section: Use Of Hg 2+mentioning
confidence: 99%
“…A large number of cyclizations are produced via transition-metal salts. Complex heterocyclic and carbocyclic compounds, which are hard to manufacture with other transition metal salts, have been successfully synthesized via cyclizations involving Hg( ii ) salts 22 Methane is converted into methanol not just in the presence of HgCl 2 . 23 But mercuric sulfate is also used as a catalyst.…”
Section: Use Of Hg 2+mentioning
confidence: 99%
“…[46] By extension, our attention focused on exploiting that unique reaction sequence as a signalling event in the recognition of electrophilic Hg 2 + ions, which have a unique ability to activate alkynes. [47] With that in mind, we devised a novel probe construct, BDP-BUS, comprising a boron-dipyrromethene (BODIPY) based fluorophore as the signalling core and an alkynyl hydrazone moiety as the Hg 2 + recognition unit. BODIPY was selected as the fluorophore for not only its outstanding photo-physical features but also its easy chemical modification.…”
Section: Introductionmentioning
confidence: 99%
“…In our sensing approach, we drew inspiration from a literature study wherein alkynyl hydrazones are reported to rapidly transform into pyrazoles via an electrophilic alkyne activation‐annulation reaction sequence (Scheme 2). [46] By extension, our attention focused on exploiting that unique reaction sequence as a signalling event in the recognition of electrophilic Hg 2+ ions, which have a unique ability to activate alkynes [47] …”
Section: Introductionmentioning
confidence: 99%